2009
DOI: 10.1038/oby.2008.614
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Copper Deficiency: A Potentially Serious and Preventable Complication Following Gastric Bypass Surgery

Abstract: Copper is an essential cofactor in many enzymatic reactions vital to the normal function of the hematologic, vascular, skeletal, antioxidant, and neurologic systems. Copper deficiency in the United States is believed to be relatively rare but has been described in the setting of zinc supplementation, myelodysplastic syndrome, use of parenteral nutrition and chronic tube feeding, and in various malabsorptive syndromes, including following gastrectomy and gastric bypass surgery. Features of copper deficiency inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 26 publications
(64 reference statements)
6
124
1
5
Order By: Relevance
“…Such patients presented with hematological or neurological symptoms, usually many years after the operations (5-21 years). In those cases, copper supplementation proved effective against anemia and neutropenia, which resolved, but neurological symptoms did not usually show full recovery [26,27] . Awareness of the risk of copper deficiency over the long term after non-bariatric gastrectomy is therefore crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patients presented with hematological or neurological symptoms, usually many years after the operations (5-21 years). In those cases, copper supplementation proved effective against anemia and neutropenia, which resolved, but neurological symptoms did not usually show full recovery [26,27] . Awareness of the risk of copper deficiency over the long term after non-bariatric gastrectomy is therefore crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, copper deficiency in bariatric surgery has mainly been reported in female patients [4,[25][26][27][28] . Buchwald et al reported in a meta-analysis that the percentage of female cases in bariatric surgery was 72.6 [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy should be avoided 12-24 months postoperatively [50]. Patients should be advised about contraception since their fertility status might be improved after weight loss [51,52].…”
Section: Clinical Nutrition Evaluation and Psychosocial-behavioral Evmentioning
confidence: 99%
“…Low plasma copper concentration and ceruloplasmin activity can be helpful to make the diagnosis. Treatment with IV copper of 2.4 mg daily for 6 days, followed by weekly intravenous copper of 2.4 mg combined with oral supplementation of 8 mg copper/daily until normal copper levels in blood are achieved was suggested [50].…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Copper is an important cofactor of enzymes involved in iron metabolism and may prevent hematologic abnormalities including anemia (GRIFFITH et al, 2009), amino acid metabolism, cholesterol and carbohydrates (MERDIVAN et al, 2004).…”
Section: Chemical Composition Of Loavesmentioning
confidence: 99%